Project-Based Learning Model Based on the Utilization of Used Goods on Students' Creative Thinking Skills on Water Cycle Materials - Lestari, Ayu; Agustiningsih; Arik Aguk Wardoyo (Universitas Negeri Surabaya, 2024)
The learning process will be more fun if it is student-centered because students are free to explore and create according to their abilities by integrating the benefits of used items as a learning medium to help students understand the water cycle material. This study aims to determine whether the creative thinking ability of grade V students is affected by a project-based learning model based on used goods. The research method used was a quasi-experimental design of the Non Equivalent Control Group pattern. The results show that students' creative thinking ability towards water cycle material is influenced by a project-based learning model based on used goods. A separate sample t-test or an independent sample t-test assisted by SPSS version 25 showed that it was 4,725 ≥ 1,988, so Ha was accepted and H0 was rejected. The scores of the experimental and control classes were both higher. according to the score of the grades obtained. However, the value of the experimental class is greater than that of the control class. The results of the TTCT study showed that the experimental score was higher than that of the control class. The conclusion of this study is that the project-based learning model based on the use of used goods affects students' creativity in water cycle materials.